THE ROLE OF SMALL BUSINESS IN ECOLOGICAL ENTREPRENEURSHIP PROJECTS AND WAYS TO INCREASE ITS EFFICIENCY - Ergashev Ulugbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article examines the importance, methods and benefits of involving small businesses in waste recycling processes. The role of the business sector in solving environmental problems and effective approaches to organizing this process are analyzed. The participation of small businesses in environmental projects contributes to the development of a culture of environmental protection in society.